The Influence of Corporate Social Responsibility (CSR) on Brand Loyalty: The Case Of Kasapreko Company Limited - Baidoo, Jocelyn Ekua (UniMAC - GIJ, 2020)
The main objective of any business is to make profit. However, businesses are realizing the importance of ensuring good relations with the societies in which they operate. To achieve this successfully, businesses are engaged in simply giving money to more complex engagements such as advocacy. CSR is a growing concept with many in academia and practice attempting to define it as they deem fit. The main objective of the study was to determine if there was a correlation between the CSR activities of a business and the loyalty of customers to that brand. The study provided literature which focused on the historical antecedent to modern theories of CSR in the developed societies and also looked at CSR in the developing world with emphasis on Ghana. The study also looked at consumer behaviour and factors affecting Consumer The study, which was based on desktop research, discovered that consumers are no longer interested in price, product or service quality and customer satisfaction as factors that motivated loyalty to a particular brand but also the “moral good” of the business. r Literature demonstrates that the practice of CSR in Ghana is mainly in certain sectors; mining, banking and telecommunications usually by multinational businesses. However, most of these activities are ad hoc in nature often at the whims of a top official within the business hence its benefits are usually not realized by beneficiaries. CSR has not been part of the corporate agenda of many companies in the developing world including Ghana. This has also affected its research hence, CSR research in developing countries is inadequate. This study is therefore adding to the body of knowledge in this field.
THESIS